A YEAR IN MY GARDEN - Kloet, Jacqueline van der (Amsterdam : HL Books, 2020)
This exceptional book immerses the reader in the world of gardens and plants. Jacqueline van de Kloet takes us on a tour of the garden in 12 chapters and shows us what makes a garden special and beautiful, month after month. She explains what has to be done throughout the year, shows us her favorite plants and gives us a glimpse into her many national and international projects. Jacqueline talks enthusiastically about her life as a garden and landscape designer and about her own little piece of paradise. The many photos are a source of inspiration and bear witness to this plantswoman's love for everything that blossoms and flourishes. The 12 recurring fixed views read as a visual narrative showing how the garden develops through the year. This is the perfect book for every garden enthusiast.
Includes index.
Keywords: Gardening; Flower gardening; Gardens -- Design